STIGMA OF ALZHEIMER'S DISEASE AND WILLINGNESS TO USE NURSING HOME AMONG KOREAN AMERICANS. (11th November 2018) - Cho, S
Abstract: The study explored the predictors of (1) feeling shame to have a dementia member in the family and (2) willingness to use a nursing home in Korean American older adults (aged 60 and older). Andersen's behavioral health model was adapted with predisposing factors (age, gender, education, acculturation), potential health needs (chronic health, self-rated health), and enabling factors (depressive symptoms, attitude towards mental health service utilization). Data were driven from a cross-sectional study of 235 community-dwelling Korean American older adults (aged 60 and older) in 2013. Logistic regression analysis showed that the likelihood of feeling shame to have a dementia member in the family increased when participants were older, and had negative attitudes towards mental health service utilization. Another set of logistic regression analysis suggested that the likelihood of willingness to use a nursing home increased when participants were acculturated more into the U.S. culture.